SEROPREVALENCE OF BOVINE VIRAL DIARRHEA VIRUS IN GRAZING CATTLE IN CAJAMARCA, PERU - Herrera R., Antonio (2011)
The aim of this study was to determine the seroprevalence of Bovine Viral Diarrheavirus (BVDV) in grazing cattle without history of vaccination, in the province of SanPablo, Cajamarca, Peru. It was used 385 samples from the serum bank, collected in 2004.Samples were stratified in four age groups (2 to <6, 6 to <12, 12 to <24, and >24 months)and by sex. The detection of antibodies against BVDV was done by the viral neutralizationtest. The 27.0 ± 4.4% (104/385) of samples had antibodies against BVDV, and withoutstatistical difference due to age or sex; however, 71.2 ± 8.7% (47/66) of animals between 12 and 24 months of age showed antibody titres between 128 and >256. It was concludedthat the BVDV is present with a low seroprevalence in the cattle population of San Pabloprovince, Cajamarca.